2014
DOI: 10.1002/2013jc009360
|View full text |Cite
|
Sign up to set email alerts
|

Suspended particulate layers and internal waves over the southern Monterey Bay continental shelf: An important control on shelf mud belts?

Abstract: [1] Physical and optical measurements taken over the mud belt on the southern continental shelf of Monterey Bay, California documented the frequent occurrence of suspended particulate matter features, the majority of which were detached from the seafloor, centered 9-33 m above the bed. In fall 2011, an automated profiling mooring and fixed instrumentation, including a thermistor chain and upward-looking acoustic Doppler current profiler, were deployed at 70 m depth for 5 weeks, and from 12 to 16 October a long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
58
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(66 citation statements)
references
References 77 publications
5
58
0
Order By: Relevance
“…Both the maximum onshore and offshore transport, as well as the effective cross-shore dispersion, vary with the depth, with larger values occurring near the pycnocline and along the bottom where velocities induced by wave breaking are strongest. The layer of particles transported offshore by the intrusion of mixed fluid after breaking resembled an INL, as observed in previous studies of wave breaking on slopes in the field (McPhee-Shaw et al 2004;McPhee-Shaw 2006;Cheriton et al 2014), in the laboratory (Ivey & Nokes 1989;Helfrich 1992;McPhee-Shaw & Kunze 2002;Nakayama & Imberger 2010) and in numerical models (Bourgault et al 2005(Bourgault et al , 2014Nakayama & Imberger 2010). In order to visualize the INL, an intermediatedensity region was defined within 0.7 ρ of ρ 0 .…”
Section: Discussionmentioning
confidence: 79%
“…Both the maximum onshore and offshore transport, as well as the effective cross-shore dispersion, vary with the depth, with larger values occurring near the pycnocline and along the bottom where velocities induced by wave breaking are strongest. The layer of particles transported offshore by the intrusion of mixed fluid after breaking resembled an INL, as observed in previous studies of wave breaking on slopes in the field (McPhee-Shaw et al 2004;McPhee-Shaw 2006;Cheriton et al 2014), in the laboratory (Ivey & Nokes 1989;Helfrich 1992;McPhee-Shaw & Kunze 2002;Nakayama & Imberger 2010) and in numerical models (Bourgault et al 2005(Bourgault et al , 2014Nakayama & Imberger 2010). In order to visualize the INL, an intermediatedensity region was defined within 0.7 ρ of ρ 0 .…”
Section: Discussionmentioning
confidence: 79%
“…Over the southern shelf, significant sediment resuspension occurs during surface wave events lasting 2–3 days and during the active passage of nonlinear internal solitary waves over the shelf and slope [ Carter et al ., ; Cheriton et al ., ]. Bottom shear stresses from tidal currents alone rarely exceed resuspension thresholds but are important in establishing a “background” shear level over which surface and internal wave events build upon [ Cheriton et al ., ].…”
Section: Study Locationmentioning
confidence: 99%
“…Cheriton et al . [] proposed that while surface waves and tidal currents play important roles in mobilizing sediment into the benthic boundary layer (BBL), updraft events may be responsible for lifting sediment out of the BBL and into the interior water column.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…6 More broadly, a wide variety of field studies have pointed to a link between increased near-bed sediment concentrations and shoaling internal waves on a slope. [18][19][20][21][22] Quaresma et al 8 have offered clear evidence of nonlinear internal waves influencing sediment resuspension over the northern shelves of Portugal. Bottom shear stress calculations suggested that the strongest nonlinear internal waves were capable of suspending sediment.…”
Section: Introductionmentioning
confidence: 99%